Prodromus of a fern flora for Bolivia. XXVI. Dennstaedtiaceae - Schwartsburd, Pedro B.; Navarrete, Hugo; Smith, Alan R.; Kessler, Michael (Phytotaxa, 2017)
We provide a synopsis to the family Dennstaedtiaceae in Bolivia, including 30 species in 7 genera. Two endemic species of Hypolepis, H. periculosa and H. woodii, and a widespread subspecies of Pteridium esculentum, subsp. gryphus, are described as new.